The mediating role of self-efficacy between workplace violence and PTSD among nurses in Liaoning Province, China: A cross-sectional study - Lu, Jiachen; Yu, Yingying; Wang, Bin; Zhang, Yanni; Ji, Haoqiang; Chen, Xu; Sun, Meng; Daun, Yuxin; Pan, Yuanping; Chen, Yunting; Yi, Yaohui; Dou, Xiaofeng; et al. (Frontiers in Psychology, 2023)
Purpose Nurses are at high risk for workplace violence, which can lead to psychological problems. The purpose of this study was to determine the relationship between workplace violence, self-efficacy, and PTSD, and to further explore whether self-efficacy mediates the relationship between workplace violence and PTSD among Chinese nurses. Materials and methods This cross-sectional study was conducted in Liaoning Province, China in 2020. A total of 1,017 valid questionnaires were returned. Each questionnaire included the Workplace Violence Scale, the General Self-Efficacy Scale, the Post-traumatic Stress Disorder Scale (PTSS-10), and demographics information. A hierarchical multiple regression approach was used to explore the mediating role of self-efficacy in the relationship between workplace violence and PTSD. The mediation model was then tested by the PROCESS macro in SPSS. Results A total of 1,017 nurses were included in this study, and the average score of PTSD among Chinese nurses was 26.85 ± 13.13 (mean ± SD). After further adjustment for control variables, workplace violence was positively associated with PTSD, explaining 13% of the variance. High self-efficacy was associated with low PTSD, explaining 18% of the variance. Self-efficacy partially mediated the role of workplace violence and PTSD. Conclusion The high scores of PTSD among Chinese nurses demand widespread attention. Workplace violence is an important predictor of PTSD in nurses. Self-efficacy is a significant factor in improving PTSD in nurses and mediates the relationship between workplace violence and PTSD. Measures and strategies to improve self-efficacy may mitigate the effects of workplace violence on PTSD in nurses.